2016
DOI: 10.1371/journal.pone.0161270
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis Inhibitors Did Not Interfere with Long-Term Depression Induced either Electrically in Juvenile Rats or Chemically in Middle-Aged Rats

Abstract: In testing the hypothesis that long-term potentiation (LTP) maintenance depends on triggered protein synthesis, we found no effect of protein synthesis inhibitors (PSIs) on LTP stabilization. Similarly, some studies reported a lack of effect of PSIs on long-term depression (LTD); the lack of effect on LTD has been suggested to be resulting from the short time recordings. If this proposal were true, LTD might exhibit sensitivity to PSIs when the recording intervals were enough long. We firstly induced LTD by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 94 publications
(153 reference statements)
0
1
0
Order By: Relevance
“…The initiation and expression of different synaptic plasticity forms involve the activation of glutamatergic receptors like AMPA and NMDA (Collingridge et al, 2004; Vishnoi et al, 2015). LTD induction is predominantly mediated with the help of NMDAR activation in the hippocampal CA1 region (Abbas, 2016). Recent studies have shown that ionotropic NMDAR signaling in the CA1 region is responsible for LTD induction rather than metabotropic NMDAR signaling, and Ca 2+ ion influx through NMDAR is necessary for LTD induction in the hippocampus (Babiec et al, 2014; Peng et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The initiation and expression of different synaptic plasticity forms involve the activation of glutamatergic receptors like AMPA and NMDA (Collingridge et al, 2004; Vishnoi et al, 2015). LTD induction is predominantly mediated with the help of NMDAR activation in the hippocampal CA1 region (Abbas, 2016). Recent studies have shown that ionotropic NMDAR signaling in the CA1 region is responsible for LTD induction rather than metabotropic NMDAR signaling, and Ca 2+ ion influx through NMDAR is necessary for LTD induction in the hippocampus (Babiec et al, 2014; Peng et al, 2010).…”
Section: Discussionmentioning
confidence: 99%